COMPARISON OF THE ANTIFUNGAL ACTIVITY OF BLACK, WHITE, AND GREEN TEA KOMBUCHA EXTRACTS AGAINST DERMATOPHYTE FUNGI - Brizzotti-Mazuchi, Natalia Seron; Lemes, Thiago Henrique [UNESP]; Siqueira, João Paulo Zen; Ribeiro-Marques, Mariela Domiciano; Maschio-Lima, Taiza [UNESP]; Polaquini, Carlos Roberto [UNESP]; Nascentes, Julyanna Andrade Silva [UNESP]; de Assis, Leticia Ribeiro [UNESP]; dos Santos Theodoro, Reinaldo [UNESP]; Regasini, Luis Octavio [UNESP]; Paziani, Mario Henrique; Kress, Márcia Regina von Zeska; et al. (Slovak University of Agriculture in Nitra, 2024)
Kombucha is obtained by fermentation of tea and sugar by bacteria and yeast. This beverage has several beneficial effects, including antimicrobial activity. The objective of this study was to evaluate the antifungal activity of Kombucha extracts against dermatomycosis-causing fungi. Different types of Kombucha (black, white, green tea) and times of fermentation (10, 20, 30 days) were evaluated. Kombuchas were filtered, and extracts obtained by liquid-liquid extraction with ethyl acetate. Minimum inhibitory concentrations (MIC) were determined against clinical isolates of dermatophytes Trichophyton rubrum and T. mentagrophytes by broth microdilution. Toxicity tests and high-performance liquid chromatography (HPLC) were also performed. MIC ranged from 62.5–2000 μg/mL. Green tea Kombucha and 10-days fermentation extracts showed the best results. Toxicity was observed only for white tea Kombucha. Despite the chromatographic profiles, further studies are needed to characterize the active molecules. However, Kombucha extracts may constitute a viable alternative for new treatment strategies against dermatomycosis.
Keywords: Antifungal susceptibility testing; Dermatophytosis; Kombucha; Liquid-liquid extraction; Trichophyton mentagrophytes; Trichophyton rubrum